Gestão de Desempenho: uma proposta para uma instituição federal de ensino superior - Vinicius de Oliveira Lopes Echeverria (2024)
This study was carried out with the aim of proposing a performance management model for technical administrative staff at a Brazilian federal higher education institution. To do this, it was necessary to understand how the processes are perceived by people who work in the sector responsible for verifying the results of these procedures. A theoretical basis was developed on the subject of performance evaluation, its cycle in Brazilian public administration and in federal universities, existing models, criteria and performance management. This work is classified as exploratory and descriptive, with bibliographical research and data collection using interviews, whose questions were created based on theory. The data obtained from the data collection was analyzed using the content analysis method. The results showed that: the current performance appraisal model is old, there is fear on the part of the appraiser in analyzing subordinates, the focus of the process is mainly on merit progression and there is no performance management model in the institution. performance management model in the institution.